(untitled) (Journal of International Studies, 2023)
When the UAE and Israel decided to normalize diplomatic relations, later known as the Abraham Accords, the decision sparked global controversy, especially from Islamic countries. One of the countries which vehemently condemned this deal was Iran. Iran viewed the agreement as a form of betrayal of the Palestinian struggle. However, based on an analysis using the Balance of Threat theory, this article concluded that Iran had in fact caused UAE’s decision to normalize relations. It was because Iran, through its superiority of aggregate power, geographical proximity, and offensive policy character, presented a serious threat to the security of the UAE. Thus, the normalization of relations with Israel was the best and rational choice for the UAE in dealing with the Iranian threat. Through this normalization, the UAE has gained a new partner to jointly counterbalance Iran’s power and help in efforts to strengthen its own defense forces.